Study of metabolic syndrome in schizophrenic patients treated with antipsychotics - Subedi, Anil; Lamichhane, Ram Prasad; Khattri, Jai Bahadur (Journal of Chitwan Medical College, 2020)
Background: There are limited data on the prevalence of metabolic side effects with the antipsychotic drugs in Nepal. The objective was to study the prevalence of metabolic syndrome in schizophrenia patients treated with antipsychotics drugs. The second objective was to test the relationship of metabolic syndrome with different socio-demographic and clinical variables Methods: This was hospital based cross sectional study conducted in the outpatient’s unit of Department of Psychiatry, Manipal Teaching Hospital, Pokhara. Ethical approval was taken from the Institutional Review Committee of Manipal College of Medical Sciences, Pokhara. A total of 60 patients (age between 16 and 65 years) who had fulfilled the diagnostic criteria of schizophrenia according to International Classification of Disease – 10 guidelines and who had taken a single antipsychotic drug for at least 6 months were enrolled after taking informed written consent. Data were collected from April 2020 to July 2020.Patients were diagnosed to have metabolic syndrome according to adapted National Cholesterol Education Program Adult Treatment Panel III criteria by the American Heart Association (NCEP ATP III-A). Data entry and analysis was done using SPSS version 16.0. The statistical method used were percentage and chi-square test. Results: The prevalence of metabolic syndrome was 30%. There was association of metabolic syndrome with socioeconomic status. There was no statistical association of metabolic syndrome with gender, residence, type and duration of antipsychotics use. Conclusions: The prevalence of metabolic syndrome was high. Therefore, proper monitoring of metabolic syndrome and adequate treatment of cardio-metabolic risk factors are required for optimum long-term management.